The philosophical rupture of Hannah Arendt (2018)
The purpose of this article is to know the essence of reflexive judgment, based on the studies developed for Hannah Arendt, who revised its minimum elements for the importance in the community building. Project developed from the academic journey that she developed about this concept, visualizing the two definitions, the first was to describe before the judgment of a Lieutenant Colonel Nazi and its modification was after this judicial process. Conceptual evolution will make it possible to identify why reflexive judgment is so important to achieve life in society.